ANALISIS KONFLIK TOKOH DALAM NOVEL RINDU KARYA TERE LIYE BERDASARKAN PENDEKATAN PSIKOLOGI SASTRA - Tiyas Sukma Melati; Pipit Warisma; Mekar Ismayani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study examines the Character Conflict in Novel Rindu Karya Tere Liye. This novel depicts the events of human life that make the pilgrimage journey, but many save physical, social and mental conflicts. The problem that was studied about the conflict that was passed by the characters in the novel Rindu Karya Tere Liye. This study discusses to reveal a picture of character conflict in the novel Rindu by Tere Liye. This research includes library research. The method used in this study is a qualitative descriptive method using psychological discussion. The data used in this study is text that contains information about the characters in the novel Rindu by Tere Liye. The source of data in this study is Novel Rindu Karya Tere Liye published by Gramedia Main Library in 2014 with 544 pages. The technical data used is the technique of reading and recording. This Rindu novel by Tere Liye is an external and internal conflict. Internal conflicts consist of 2 and physical conflicts 3, while internal conflicts are internal conflicts or 5. It can be concluded that conflicts occur in inner conflicts.